KAJIAN TERHADAP PENGEMBANGAN HUTAN RAKYAT DI KABUPATEN WONOGIRI (A Study on the Fann Forest Development in Wonogiri) - , Kristanto Adiputranto ([Yogyakarta] : Fak. Kehutanan UGM, 2000)
Recently the fann forest in Wonogiri District has been able to provide economic and non-economic benefits to the owner. This fann forest is generally planted in dry land as one ofthe alternatives to solve the dry land agricultural problems. Among the problems are: variation of the land topography, poor land fertility, variation of land terrain, variation of the climate which gives the difficulties in arranging the planting time, and lack of water. The existence ofthe fann forest is hoped to be able to give the optimal productivity of agriculture, to provide protection to the low land area and to increase the people-prosperity and the effort to spread out the development The community forest in Wonogiri District covers totally 15 320.5 ha and has a capacity of producing wood of972 539.93 mJ. The average production per year for lumber and firewood is 4.9 mJ/ ha and 15.9 m3fha, respectively. In addition, there are also other benefits such as seed and leaves, and also indirect benefit such as water resource. A number of problems are still being encountered in developing the community forest: poor quality of seed, improper silviculture practices. the need to abide the government regulation in forestry product, lack of capital, and limited capability and knowledge of responsible government agency for . private forest development. The success of the fann forest development can only be achieved through the transitional process in transforming the culture oftraditional society to that of modern- business oriented. The success can not be seen from the physical aspect only, but it can be perceived from other aspects as well, such as the increase of skill and knowledge of the fanners in managing the forest, the improvement of society discipline in conservation effort, the high solidarity among the fanners to help one another, and the betterment offanner's view in developing their fanning business.